Самый счастливый день: [повести, романы] / Виктория Токарева - Токарева Виктория Самойловна (Очарованная душа, 1998)
Экземпляры: ф. 19 (20231226) / Инвентарный номер: 66963 / Цена: 10.00 / Авт.знак: Т 51 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6